Recent Advancements in Robotic-assisted Plastic Surgery Procedures: A Systematic Review - Kazuho Kawashima, MD; Shadi Ghali, MD, FRCS (Plast); Dariush Nikkhah, MD, FRCS (Plast); Ali Esmaeili, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. There has been a delayed, yet steady uptake of robotic-assisted surgery over the past decade within the field of plastic surgery. In an era of rapidly evolving scientific and technological development, there is a need for an update on the current literature for robotic-assisted plastic surgery procedures. Methods:. Searches were conducted across major databases, including MEDLINE, Embase, and Central for published literature from March 2023 to December 2024. Only published articles written in English with full texts were considered for the final narrative synthesis. Results:. Initially, we identified 1200 articles in the database search. Subsequently, 46 articles were included in our final narrative synthesis. Among the selected studies, 4 focused on reconstruction in transoral robotic surgery, 14 on breast surgery, 10 on robotic microsurgery, 5 on abdominal wall reconstruction, 6 on vaginoplasty, and 5 on flap harvest. Conclusions:. The evidence to support the advantage of robotic plastic surgery procedures over traditional methods is relatively weak. However, there have been some advancements, specifically in transoral robotic surgery, robotic mastectomy, and breast reconstruction. Nevertheless, comprehensive exploration and prospective randomized trials are essential across all procedures to define the role of surgical robots in plastic surgery. The impediments to wider adoption include high costs, disruption to operative flow, and the absence of haptic feedback in robotic-assisted procedures within the specialty.